2011
DOI: 10.5047/eps.2011.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Shallow inland earthquakes in NE Japan possibly triggered by the 2011 off the Pacific coast of Tohoku Earthquake

Abstract: Shallow seismic activity in the crust of the overriding plate west of the source area increased significantly after the 2011 M w 9.0 Tohoku earthquake which ruptured the plate boundary to the east off northern Japan beneath the Pacific Ocean. In order to understand the cause of this distinctive change in seismicity, we have precisely relocated earthquake hypocenters for several earthquake sequences that occurred during the period March 11-April 6, 2011, following the Tohoku earthquake by the double-difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…It is remarkable that such a seemingly small stress drop changed the state of stress in the offshore forearc from predominantly margin‐normal compression to tension. The stress reversal was documented by a number of studies through analyses of focal mechanisms of small earthquakes off the megathrust before and after the earthquake (Asano et al, ; Hasegawa et al, ; Nakamura et al, ; Okada et al, ; Yoshida et al, ). Results from Hasegawa et al () and Nakamura et al () along a central corridor (Figure a) are shown in Figure .…”
Section: Stress Change In the Forearc Caused By The Earthquakementioning
confidence: 99%
“…It is remarkable that such a seemingly small stress drop changed the state of stress in the offshore forearc from predominantly margin‐normal compression to tension. The stress reversal was documented by a number of studies through analyses of focal mechanisms of small earthquakes off the megathrust before and after the earthquake (Asano et al, ; Hasegawa et al, ; Nakamura et al, ; Okada et al, ; Yoshida et al, ). Results from Hasegawa et al () and Nakamura et al () along a central corridor (Figure a) are shown in Figure .…”
Section: Stress Change In the Forearc Caused By The Earthquakementioning
confidence: 99%
“…The 2011 M w 9.0 Tohoku earthquake, Japan, generated more than 50 m of slip on the interface between the subducting Pacific plate and the overriding plate (e.g., Ito et al, 2011;Simons et al, 2011;Yamazaki et al, 2011), and caused significant stress changes in the eastern half of Honshu Island, resulting in the excitation of widespread seismic activity (e.g., Okada et al, 2011; and changes in the type of focal mechanisms in and around the focal area (Asano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Tohoku‐oki earthquake brought stress changes and consequent seismicity changes in and around the source region [e.g., Toda et al , ; Hasegawa et al , ; Okada et al , ]. For example, in the area that underwent large coseismic slip during the 2011 Tohoku‐oki earthquake, the number of interplate and repeating earthquakes has been reported as having dramatically decreased after the M 9 earthquake [e.g., Asano et al , ; Kato and Igarashi , ; Uchida and Matsuzawa , ].…”
Section: Introductionmentioning
confidence: 99%